Visible Light Responsive Photoassisted Electrocatalytic System Based on CdS NCs Decorated TiO2 Nano-tube Photoanode and Activated Carbon Containing Cathode for Wastewater Treatment. (20th February 2015) - Cheng, Xiuwen; Pan, Guoping; Yu, Xiujuan
Graphical abstract: Highlights: CdS NCs/TiO2 NTs photoelectrodes were fabricated through anodization, followed by electrodeposition strategy. The photoelectrochemical properties of CdS NCs/TiO2 NTs photoelectrode were studied. An efficient and stable PEC system based on CdS NCs/TiO2 NTs photoanode and AC/PTFE cathode was constructed. Contribution of each reactive species on PEC degradation of pollutants was distinguished. The enhanced PEC mechanism of PEC system were proposed and confirmed. Abstract: In this study, CdS NCs decorated TiO2 nano-tubes (CdS NCs/TiO2 NTs) photoelectrode was fabricated through anodization, followed by electrodeposition strategy. The resulting samples were characterized by SEM, XPS, UV–vis DRS and photoelectrochemical (PECH) measurements. It was found that the CdS NCs/TiO2 NTs photoelectrode exhibited intense visible light absorbance ranging from 400–700 nm and high transient photocurrent density of 9.62 mA cm −2 . Furthermore, AC/PTFE cathode was prepared by rolling the AC and PTFE latex on a machine with the stainless steel as support. Subsequently, an effective and stable PEC system based on the as-fabricated CdS NCs/TiO2 NTs photoanode and AC/PTFE cathode was constructed for the degradation of RhB. Results showed that with the help of +2.0 V external potential, the PEC system exhibited superior PEC performance, in which 97.5% of RhB could be degraded. In addition, the generation rate of OH radicals and contribution of each reactive species to the PEC efficiency were also detected. Therefore, the efficient and stable PEC system based on CdS NCs/TiO2 NTs photoanode and AC/PTFE cathode could be a versatile candidate in pollutants elimination and water splitting.